Proceedings of the 2019 Ramazzini Days: Session I - Casale Monferrato: Lessons learned and the road ahead - VV, AA (European Journal of Oncology and Environmental Health, 2019)
1. Casale Monferrato: Lessons learned and the road ahead L. Christine Oliver, USA 2. A community in need of a novel approach to cure and care Daniela Degiovanni, Italy 3. Focus on clinical and translational research in the mesothelioma unit of Alessandria and Casale Monferrato Hospitals Federica Grosso, Italy 4. Asbestos related diseases epidemiology and surveillance in Italy: Road ahead and still open questions Alessandro Marinaccio, Italy 5. Criminal prosecution of business executives for occupational cancer in Italy Barry Castleman, USA